2020
DOI: 10.1108/jcrpp-02-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

“Understanding my story”: young person involvement in formulation

Abstract: Purpose The SECURE STAIRS framework has promoted young person involvement as a key feature of innovative service provision. In the North East of England, Secure Children’s Homes (SCHs) have pioneered young person involvement in team formulation. Young people have also led on the development of formulation materials through a young person involvement project. Young people’s attendance at team formulation meetings has become embedded. These service developments have also begun to expand across broader SCHs, Secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Previous research has indicated that the formulation-led approach promoted by the SECURE STAIRS framework can enhance staff confidence and knowledge regarding the young people that they are working with, particularly when the young person is present. McKeown et al (2020) found that staff attending young person formulations within a SCH where the young person was present expressed significant improvements in their knowledge, motivation and confidence with supporting the young person, as well as enhanced satisfaction with the treatment plan. The increase in EssenCES scores after the depletion during the pandemic may also have been impacted by the enhanced formulation-led support that was provided during this time, following principles of the SECURE STAIRS framework to enable containment and therapeutic relationships during a time of uncertainty.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has indicated that the formulation-led approach promoted by the SECURE STAIRS framework can enhance staff confidence and knowledge regarding the young people that they are working with, particularly when the young person is present. McKeown et al (2020) found that staff attending young person formulations within a SCH where the young person was present expressed significant improvements in their knowledge, motivation and confidence with supporting the young person, as well as enhanced satisfaction with the treatment plan. The increase in EssenCES scores after the depletion during the pandemic may also have been impacted by the enhanced formulation-led support that was provided during this time, following principles of the SECURE STAIRS framework to enable containment and therapeutic relationships during a time of uncertainty.…”
Section: Discussionmentioning
confidence: 96%
“…The current findings indicated significantly more psychological formulation and formulation attendees after lockdown; the number of incidents were also significantly negatively associated with the number of formulation meetings. Being a part of team formulation enables staff to recognise and understand potential relational and developmental processes that could be underlying certain behaviours and supports staff teams to develop psychological understanding and strategies to work with the young person (Kustner, 2019; McKeown et al , 2020). Team formulations also provide a reflective space where incidents and challenging behaviour can be explored; developing a shared understanding provides the young person with a consistent approach (Christofides et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased case formulation meetings were provided and further reflective practice opportunities were offered to staff. Previous research within the setting has identified that formulation meetings significantly increase staff knowledge, confidence, motivation and understanding of young people (McKeown et al , 2020). Resources promoting mindfulness, sleep hygiene and coping strategies to manage any anxiety originating from the pandemic were distributed for young people within the setting. Technological developments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited research in the domain of young person involvement in formulation. Of limited research that exists, there are indications that young person involvement in the process is helpful (McKeown et al , 2020; Milson and Phillips, 2015). In terms of evaluation of formulation directions, young people involvement in this process is also an important consideration.…”
Section: Young Person Involvement In Formulationmentioning
confidence: 99%